Proposta de equação para determinar a eficiência apresentada por inversores de SFVCR para as condições de irradiância encontradas no estado do Paraná - Santos, Telma Aparecida Meneghette dos (2021)
Photovoltaic Energy is considered a fundamental element when it comes to sustainable and clean energy. Developed countries already have solar energy as a considerable part of their energy mix. On the other hand, the actions in Brazil towards this topic are at early stage, but with an outstanding upcoming growth perspective in the next years due to proper solar radiation distribution in the country territory. In this scenario, it is relevant to study implementation conditions and photovoltaic inverter conversion efficiency considering solar radiation for Brazilian particularities. Starting from several efficiency equations were studied, including European and California models, this work ion. Considering Inverter Efficiency Equations for Photovoltaic systems throughout the world, mainly Californian and European models which were originated from data captured from a single location, this study gathers the 11year database of radiation in the state of Paraná in southern Brazil in several locations in order to raise the irradiance behavior in the state and propose an efficiency equation based on territorial characteristics. This method reveals less variation and more assertive results than the other international equations. With this equation, it is possible to understand the behavior of market inverters in the region and show which characteristics are desirable.